IMPLEMENTATION OF E-GOVERNMENT STRATEGIES In PAREPARE CITY USING CASSIDY MODEL AND DIMENSIONS OF INDONESIA E-GOVERNMENT RANKING - IMPLEMENTASI STRATEGI E-GOVERNMENT KOTA PAREPARE MENGGUNAKAN MODEL CASSIDY DAN DIMENSI PEMERINGKATAN E-GOVERNMENT INDONESIA (PeGI) - Firdaus Masyhur (Jurnal Penelitian Komunikasi dan Opini Publik, 2016)
The development of e-Government in Indonesia has started since 2003, but progress has not been able to answer the challenges and needs of the community as well as pressure from the pace of technological development. This study is an effort to strategize the implementation of e-Government in Parepare to realize governance with the effective use of information technologyin accordance with the vision of Parepare to be a cyber city. The method used is the combination of Cassidy Model and Dimensionsof PeGI. The dimensions is used to limiting the scope and direct the process and results to produce a strategy implementation of comprehensive e-Government. Bureaucratic Reform Program is also used as a reference, especially in managing the business processes of public services in the Parepare City.This study generates recommendations from the policy, institutional, applications, infrastructure, and planningdimensions.This strategy was later embodied in the policy of the Master Plan for Information and Communication Technology (RITIK) Parepare guiding along Bureaucracy Reform Team and Unit of Work in the Field of Communication and Information.Keywords:e-Government, Cassidy Model, PeGI, Bureaucracy ReformPengembangan e-Government di Indonesia telah dimulai sejak tahun 2003, namun perkembangannya hingga saat ini belum mampu menjawab tantangan dan kebutuhan masyarakat serta tekanan akibat laju perkembangan teknologi yang sangat pesat. Penelitian ini merupakan upaya dalam menyusun strategi implementasi e-Government di Kota Parepare untuk mewujudkan pemerintahan dengan pemanfaatan teknologi informasi yang efektif sesuai dengan visi Kota Parepare untuk menjadi kota cyber. Metode yang digunakan mengkombinasikan Model Cassidy dan Dimensi PeGI. Dimensi-dimensi PeGI digunakan untuk membatasi rung lingkup serta mengarahkan proses dan hasil penelitian sehingga menghasilkan sebuah strategi implementasi e-Government yang komprehensif. Program Reformasi Birokrasi juga dijadikan acuan implementasi khususnya dalam menata proses bisnis layanan publik yang ada di Kota Parepare. Penelitian ini menghasilkan rekomendasi dari dimensi kebijakan, kelembagaan, aplikasi, infrastruktur, dan perencanaan. Strategi ini kemudian diwujudkan dalam kebijakan Rencana Induk Teknologi Informasi dan Komunikasi (RITIK) Kota Parepare yang dijadikan pedoman bersama Tim Reformasi Birokrasi dan Unit Kerja di Bidang Komunikasi dan Informatika. Kata Kunci: e-Government, Model Cassidy, PeGI, Reformasi Birokrasi